Affective responses to overeating episodes in women participating in a behavioral weight loss program. (January 2022) - Hayes, Jacqueline F.; Schumacher, Leah M.; Panza, Emily; Dunsiger, Shira I.; Wing, Rena R.; Unick, Jessica L.
Abstract: Background: Much research has focused on precursors to dietary lapses in weight loss programs, but less is known about how individual responses to lapses may influence future non-adherence and program success. The current study examined affective responses to overeating lapses and their influence on subsequent overeating and overall weight loss. Methods: Women (n = 60) with overweight or obesity (BMI (mean ± SD): 34.3 ± 3.9 kg/m 2 ; age: 48.1 ± 10.1 years) participated in a 3-month group behavioral weight loss intervention (BWLI). At baseline and 3 months, participants completed anthropometric assessments and a 10-day ecological momentary assessment protocol sent 5 times per day reporting on overeating and affect (stress, shame, anxiety, and feeling good about oneself). Across time points, multilevel models were used to examine affective responses to overeating and to predict likelihood of subsequent overeating. Linear regression models were used to examine the effect of affective responses to overeating (at baseline and collapsed across time points) on weight loss. Results: Following self-reported overeating episodes, compared to non-overeating episodes, feeling good about oneself decreased. These decreases lessened with time from overeating. Overeating predicted subsequent overeating episodes, with decreases in feeling good about oneself following overeating marginally predicting increased likelihood (p = 0.065). Neither overeating frequency at baseline nor change in overeating frequency predicted weight loss; however, greater decreases in anxiety following overeating were associated with less weight loss. Conclusions: Self-reported overeating during a BWLI was associated with negative affective responses and may have increased the likelihood of subsequent overeating, but did not affect overall weight loss in this sample. Highlights: Negative affect after overeating may perpetuate overeating in women with obesity. Feeling good about oneself is lower after overeating among weight loss program participants. Decrements in feeling good about oneself are acute and lessen over time. Neither overeating nor negative affect following overeating predicted weight loss.